Steroid sulfatase and sulfuryl transferase activities in human brain tumors - Kríz, Lubomír; Bicíková, Marie; Mohapl, Milan; Hill, Martin; Cerný, Ivan; Hampl, Richard (The Journal of steroid biochemistry and molecular biology, 2008)
Neuroactive steroids (dehydroepiandrosterone, pregnenolone) and their sulfates act as modulators of glutamate and gamma-aminobutyrate type A receptors in the brain The physiological ratio of these neuromodulators is maintained by two enzymes present in the brain, namely, steroid sulfatase (STS) and steroid sulfuryl transferase (SULT). Following previous determination of their activities in monkey brains, their activities were evaluated in human brain tumors. Radioimmunoassay and GC-MS were used for determination of products. Both enzyme activities were measured in the 55 most frequent human brain tumors (glioblastomas, pituitary adenomas, meningiomas, astrocytomas). Significant differences were found in STS activity among investigated types of tumors except the pair of pituitary adenomas-glioblastomas, while significant differences were found in SULT activity among investigated types of tumors. Spontaneous tendency to form clusters was revealed when both enzyme activities were taken as coordinates. Clustering indicated an individual metabolic behavior of glioblastomas and 72.7% of pituitary adenomas. Astrocytomas, meningiomas and remaining 27.3% pituitary adenomas showed similarities in both enzymes' activities. Differences in STS and SULT activity did not depend on the sex or age of subjects.
Keywords: Sulfotransferases; Meningeal Neoplasms; nádory mozku; nádory hypofýzy; Humans; steryl-sulfatasa; lidé středního věku; Brain Neoplasms; Meningioma; Female; dospělí; lidé; Radioimmunoassay; sulfotransferasy; radioimunoanalýza; glioblastom; Astrocytoma; Adult; Pituitary Neoplasms; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Male; Middle Aged; adenom; Adenoma; Glioblastoma; meningeom; Gas Chromatography-Mass Spectrometry; mužské pohlaví; astrocytom; meningeální nádory; Steryl-Sulfatase